Economic Assessment of the Rain-Fed Barely Crop in Salamieh: farm income of the Rain-Fed Barely Crop in Salamieh (Journal of Hama University, 2022)
The goal behind this descriptive economic study on the rain-fed crops in Salamieh District is to show the economic importance of this crop on the gross national income on one hand, and due to its excellence over a number of agricultural products in dry zones on the other. Salamieh has been chosen in this field for being dependent in the first rank on barely farming as a rain-fed farming.This study (research) is aimed to shed light on the reality and effects of the barely farming and to know the social and economic characteristics of the farmers and also the difficulties and obstacles facing those farmers.Questionnaires, data, secondary statements and primary analyses have been followed and adopted in this study which showed that the area of land planted with barely in rain-fed land have decreased in recent years on both levels: nationally and locally. One reason behind this is the current civil crisis. The research also showed that 72% of the farmers follow on agricultural course and this is a good indicator. It also showed the lack of illiteracy among the farmers of the studied sample, and this is a good indication that most farmers can deal with agricultural vocabulary and do arithmetic operations well. The high wages of the female peasants are among the prior problems which need to be resolved. This question represents 27.13%, and the high price of fertilizers represents 26.67%. no doubt, production is influenced negatively by this situation. The results also showed that the average value of the total cost of the of the Rain-Fed barley crop in Salamieh in the agricultural season 2017-2018 amounted to 10880 SP / donum, of which 7550 SP / donum were variable costs, while the fixed costs amounted to 3330 SP. SP/acres. The average yield of the of the Rain-Fed barley crop for the research sample was 17250 SP / donum, while the average profit amounted to (6370) SP / donum.
Keywords: Economic Assessment, Rain-Fed Barely, farm income.